Behavioral and Neurobiological Convergence of Odor, Mood and Emotion: A Review - Kontaris, Ioannis; East, Brett S.; Wilson, Donald A. (Frontiers in Behavioral Neuroscience, 2020)
Affective state is the combination of emotion and mood, with mood reflecting a running average of sequential emotional events together with an underlying internal affective state. There is now extensive evidence that odours can overtly or subliminally modulate mood and emotion. Relying primarily on neurobiological literature, here we review what is known about how odours can affect emotions/moods and how emotions/moods may affect odour perception. We take the approach that form can provide insight into function by reviewing major brain regions and neural circuits underlying emotion and mood and then reviewing the olfactory pathway in the context of that emotion/mood network. We highlight the extensive neuroanatomical opportunities for odour-emotion/mood convergence, as well as functional data demonstrating reciprocal interactions between these processes. Finally, we explore how the odour- emotion/mood interplay is, or could be, used in medical and/or commercial applications.